Pengaruh Kondisi Tanah Terhadap Tahanan Pentanahan Kaki Menara 150KV Kramasan-Mariana - Nurdiana, Nita; Radeli, Rieski (JURNAL SURYA ENERGY, 2022)
The grounding system is intended to ensure that both electrical equipment and the people around it are in a safe condition from overcurrent faults by transferring the fault current to earth. Electrode implantation is one of the factors to get a small grounding resistance value. This study aims to determine the effect of soil conditions on the value of grounding resistance at the foot of the Menara. By using the three-point method on three types of soil conditions at 6 feet Menara, the lowest grounding value is 5.12 ohms in the swamp area at Menara 10 location. The highest grounding resistance in the garden area is 8.32 ohm at Menara 66 location. All values the grounding resistance is in good condition and does not exceed the 150 Kilo Volt high voltage overhead line grounding standard, which is 10 ohms. From the results of the analysis, it is concluded that the soil conditions where the electrodes are implanted affect the grounding value ABSTRAKSistem pentanahan dimaksudkan untuk memastikan bahwa baik peralatan listrik maupun orang-orang disekitarnya dalam kondisi yang aman dari gangguan arus lebih dengan cara  mentransfer arus gangguan ke bumi. Penanaman elektroda merupakan salah satu faktor untuk mendapatkan nilai hambatan pentanahan yang kecil. Penelitian ini bertujuan untuk mengetahui pengaruh kondisi tanah terhadap nilai tahanan pentanahan pada kaki Menara SUTT. Dengan menggunakan metode tiga titik pada tiga jenis kondisi tanah  pada 6 kaki Menara, didapatkan nilai pentanahan terendah sebesar 5,12 ohm  di daerah rawa pada lokasi Menara 10. Hambatan  pembumpentanahan tertinggi di daerah kebun yaitu 8,32 ohm pada lokasi Menara 66. Semua nilai tahanan pentanahan dalam keadaan baik dan tidak melebihi standar pentanahan saluran udara tegangan tinggi 150 Kilo Volt yaitu sebesar 10 ohm. Dari hasil analisa diperoleh kesimpulan bahwa kondisi tanah dimana elektroda ditanamkan mempengaruhi nilai pentanahan.